(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2014)
Architectural experiences are essentially multi-sensory and simultaneous, and a complex entity is usually grasped as an atmosphere, ambience or feeling. In fact, the judgement concerning the character of a space or place calls for categories of sensing that extend beyond the five Aristotelian senses, such as the embodied existential sense, and, as a result, the entity is perceived in a diffuse, peripheral and unconscious manner. Paradoxically, we grasp an atmosphere before we have consciously identified its constituent factors and ingredients. «We perceive atmospheres through our emotional sensibility – a form of perception that works incredibly quickly, and which we humans evidently need to help us survive», Peter Zumthor suggests. We are mentally and emotionally affected by works of art before we understand them, or we may not understand them intellectually at all. Sensitive artists and architects intuit experiential and emotive qualities of spaces, places and images. This capacity calls for a specific kind of imagination, an emphatic imagination. Atmospheres are percieved peripherally through diffuse vision interacting with other sense modalities, and they are experienced emotionally rather than intellectually. The studies on the differentiation of the two brain hemispheres suggest that atmospheres are perceived through the right hemisphere. Somewhat surprisingly, atmospheres are more conscious objectives in literature, cinema, theater, painting and music than in architecture, which has been traditionally approached formally and perceived primarily through focused vision. Yet, when we see a thing in focus, we are outsiders to it, whereas the experience of being in a space calls for peripheral and unfocused perception. One of the reasons for the experiential poverty of contemporary settings could be in the poverty of their peripheral stimuli.